Rapid creation of an emergency department telehealth program during the COVID-19 pandemic. (April 2022) - Heslin, Samita M; Nappi, Michael; Kelly, Gerald; Crawford, Joan; Morley, Eric J; Lingam, Veena; Henry, Mark; Viccellio, Peter
Coronavirus disease 2019 (COVID-19) has spread to nearly every continent, with over 2.6 m cases confirmed worldwide. Emergency departments care for a significant number of patients who are under investigation for COVID-19 or are COVID-19-positive. When patients present in the emergency department, there is an increased risk of spreading the virus to other patients and staff. We designed an emergency department telehealth program for patients physically in the emergency department, to reduce exposure and conserve personal protective equipment. While traditional telehealth is designed to be patient-specific and device-independent, our emergency department telehealth program was device-specific and patient-independent. In this article, we describe how we rapidly implemented our emergency department telehealth program, used for 880 min of contact time and 523 patient encounters in a 30-day period, which decreased exposure to COVID-19 and conserved personal protective equipment. We share our challenges, successes and recommendations for designing an emergency department telehealth program, building the technological aspects, and deploying telehealth devices in the emergency department environment. Our recommendations can be adopted by other emergency departments to create and run their own emergency department telehealth initiatives.